Śrī Pushpamālā prakaraṇa - Hemacandra Sūri; Karpuravijaya. (Śrī Jinaśāsana Ārādhanā Ṭrasṭa, 1987)
Verse work, with Gujarati interpretive works, on Jainism.
Gujarati and Prakrit.
Verse work, with Gujarati interpretive works, on Jainism.
Keywords: Jainism / Doctrines / Early works to 1800 / http://id.loc.gov/authorities/subjects/sh2008105980